Korban Pemerkosaan Dalam Hal Pemenuhan Hak Aborsi Oleh Kepolisian Resor Jombang - Puspitasari, Rizki Dian; Hakim, Arief Rachman (Legal Spirit, 2025)
The emergence of pregnancy due to rape cannot be separated from the act of rape itself. Rape victims should be able to choose whether to give birth to their child or to have an abortion. It often happens that rape victims become perpetrators of criminal abortion due to a lack of information about safe and legal abortion. In reality, regulations regarding abortion for rape victims have been stipulated in the Government Regulation on Reproductive Health. The phrase “pregnancy due to rape” allows for abortion to be carried out if it complies with the provisions set by the government. This proves that there is a right to abortion for rape victims to be able to terminate their pregnancy. However, in reality, even though there are regulations that govern, the implementation of these regulations still faces obstacles and rejection. This study aims to find out the implementation of the abortion rights of rape victims based on empirical juridical research facts to find theories about the process of occurrence and the working of law within society. The legal protection that should be received by rape victims as victims in the crime of rape becomes questionable because if the rape victim has an abortion, then the victim is at risk of becoming a criminal offender. The government should indeed provide abortion rights to rape victims and strict criminal provisions regarding legal protection for rape victims who have abortions.